2021
DOI: 10.5840/ijap2022422168
|View full text |Cite
|
Sign up to set email alerts
|

Philosophy as a Way of Life for Addiction Recovery

Abstract: In this essay I explore the notion of philosophy as a way of life as a recovery pathway for individuals in addiction recovery. My hypothesis is that philosophy as a way of life can be a compelling, and legitimate recovery pathway for individuals in addiction recovery, as one of many recovery pathways. I will focus on logic-based therapy (LBT) applied in the context of addiction recovery. The aim of presenting a case study is to show how a client receiving LBT is provided with techniques and a worldview that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…14 I have previously suggested that PWL can be a compelling, and legitimate recovery pathway for individuals in addiction recovery, as one of many recovery pathways. 15 Considering that there is an ostensibly low efficacy rate for the treatment of addiction, articulating the value of PWL as a recovery pathway provides a conceptual and methodological framework for the development of novel philosophically-based addiction treatment and recovery-oriented programs--thus expanding the treatment and recovery options available for those seeking recovery from addiction. There are few books that promote the value of philosophy in addiction recovery, 16 and that fosters a conversation between philosophy and Twelve-step spirituality, 17 and Stoic and Buddhist philosophies have been applied within the context of addiction recovery.…”
Section: Friedrich Nietzsche -Thus Spoke Zarathustramentioning
confidence: 99%
See 1 more Smart Citation
“…14 I have previously suggested that PWL can be a compelling, and legitimate recovery pathway for individuals in addiction recovery, as one of many recovery pathways. 15 Considering that there is an ostensibly low efficacy rate for the treatment of addiction, articulating the value of PWL as a recovery pathway provides a conceptual and methodological framework for the development of novel philosophically-based addiction treatment and recovery-oriented programs--thus expanding the treatment and recovery options available for those seeking recovery from addiction. There are few books that promote the value of philosophy in addiction recovery, 16 and that fosters a conversation between philosophy and Twelve-step spirituality, 17 and Stoic and Buddhist philosophies have been applied within the context of addiction recovery.…”
Section: Friedrich Nietzsche -Thus Spoke Zarathustramentioning
confidence: 99%
“…18 But research that specifically argues for PWL (as articulated by Hadot) as a legitimate addiction recovery pathway has only recently been suggested. 19 I also suggest that LBT may be a particularly suitable intervention when challenging the unrealistic conclusions derived from illogical premises in practical reasoning that contribute to addiction, because it can contest irrational beliefs in a way that could mitigate the fragmentation anxiety that often arises when individuals relinquish maladaptive selfobject organizations.…”
Section: Friedrich Nietzsche -Thus Spoke Zarathustramentioning
confidence: 99%